3.相同温度下: 2H2(g)+S2(g) ⇌ 2H2S(g) Kp1 2Br2(g)+2H2S (g) ⇌ 4HBr(g)+S2(g) Kp2 Br2(g)+H2 (g) ⇌ 2HBr(g) Kp3 则Kp2等于( )。A. Kp1· Kp3 B. (Kp3)2/ Kp1 C. 2Kp1· Kp3 D. Kp3/ Kp1
A: 错
B: 对
C: 错
D: 错
A: 错
B: 对
C: 错
D: 错
举一反三
- 11.某温度时H2(g)+ Br2(g)⇌2HBr(g)的Kp=4×10-2,则反应HBr(g)⇌1/2H2(g)+1/2 Br2(g)的Kp是( B)。 A: 1/4×10-2 B: 1/[(4×10-2)1/2] C: (4×10-2)1/2 D: 2×10-1
- 已知:2H2(g)+S2(g)=2H2S(g) Kp1 2Br2(g)+2H2S(g)=4HBr(g)+S2(g) Kp2 H2(g)+Br2(g)=2HBr(g) Kp3 则Kp3等于( )
- 已知: 2H2(g) + S2(g) = 2H2S(g) Kp1 2Br2(g) + 2H2S(g) = 4HBr(g) + S2(g) Kp2 H2(g) + Br2(g )= 2HBr(g) Kp3 则 Kp3等于( )
- 已知: 2H2(g) + S2(g) = 2H2S(g) Kp1 2Br2(g) + 2H2S(g) = 4HBr(g) + S2(g) Kp2 H2(g) + Br2(g )= 2HBr(g) Kp3 则 Kp3等于( )
- 已知:2H2(g)+S2(g)=2H2S(g)Kp1 2Br2(g)+2H2S(g)=4HBr(g)+S2(g)Kp2 H2(g)+Br2(g)=2HBr(g)Kp3 则Kp3等于()